Kajian Pola Tanam Tumpangsari Selada Crop-Tomat dan Mulsa Jerami pada Pertumbuhan dan Hasil Tanaman - H. Pujisiswanto; D. Pangaribuan (Politeknik Negeri Lampung., 2010)
The research was to study the interaction between crop lettuce and tomato under intercropping system, its effect straw mulch on growth and yield of both crop. The experiment was conducted at the Mujimulyo village, Natar. The experiment was conducted from April until July 2008. The Strip Plot Design was used with two factors and three replication. Intercropping followed additive series system: the first factor was croppings, i.e.: crop lettuce 100%, crop lettuce 75% : tomato 25%, crop lettuce 50% : tomato 50%, crop lettuce 25%: tomato 75%, and tomato 100%.The second factor was straw mulch, i.e.: no mulch, 4 and 8 ton ha-1. Experimental results showed that: (1) Straw mulch treatment did not effect on growth and plant yield, but croppings conferred effect to plant yield. (2) In intercrop, the two crop interacted leading to an increase of tomato yield but a decrease in crop lettuce. Graph of the replacement series indicated a compensation with respect to crop yield. (3) The best scheme with regard to yield was 50%:50% intercrop as it had a retative yield total 1,17. Keywords : interaction, straw mulch, crop lettuce, tomato, intercropping.